Synthesis, magnetospectral, and thermal studies of cobalt(II), nickel(II), and copper(II) complexes of new asymmetrical 1,2-dihydroxyimino-3,8-diaza-9-phenylnonane - Sekerci, M (Interperiodica, 2000)
vic-Dioximes have great importance since they are used as chelating agents because of their stable complexes with transition metals. 1-Amino-4-(N-benzylamino)butane (1) has been obtained by the reaction of benzyl chloride and 1,4-diaminobutane. In a second step, 1,2-dihydroxyimino-3,8-diaza-9-phenylnonane (2) has been obtained by the reaction of (1) with anti-chloroglyoxime. Ligand 2 reacted with transition metals such as Ni(II), Co(II), and Cu(II). The Cu(II) and Ni(II) complexes of these ligands are proposed to be square-planar, while the Co(II) complexes are proposed to be octahedral with two water molecules as axial ligands because of the data of elemental analyses, infrared and H-1 NMR spectra, magnetic measurements, TGA and DTA techniques.
Keywords: Amine Oxime Ligands; Molecular-Structure; Metal Complexation; Crystal-Structures; Palladium(Ii); (E,E)-Dioximes; Platinum(Ii); Mononuclear; Uranyl(Vi)